2022
DOI: 10.3389/fmicb.2022.933722
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of Rhizosphere Microbiota Associated With Rice Genotypes Differing in Aluminum Tolerance in an Acid Sulfate Soil

Abstract: Rhizosphere microbes are important for plant tolerance to various soil stresses. Rice is the most aluminum (Al)-tolerant small grain cereal crop species, but the link between rice Al tolerance and rhizosphere microbiota remains unclear. This study aimed to investigate the microbial community structure of aluminum-sensitive and Al-tolerant rice varieties in acid sulfate soil under liming and non-liming conditions. We analyzed the rice biomass and mineral element contents of rice plants as well as the chemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…These differences were easily visualized in the NMDS ordination plot (Figures 1 and 2) where it has been shown the important role of a plant genotype as key determinant of the microbial assemblage. Similar results were shown in different specie varieties of maize [24], barley [25], wheat [26], soybean [27], cotton [28], or rice [29]. Nonetheless, there was no significant effect of the purslane genotype on alpha diversity (Shannon index and ASV richness), either for bacteria or fungi, except for fungal richness that was significantly higher in the Spanish (wild) purslane rhizosphere (F = 18.4, p < 0.001).…”
Section: Resultssupporting
confidence: 77%
“…These differences were easily visualized in the NMDS ordination plot (Figures 1 and 2) where it has been shown the important role of a plant genotype as key determinant of the microbial assemblage. Similar results were shown in different specie varieties of maize [24], barley [25], wheat [26], soybean [27], cotton [28], or rice [29]. Nonetheless, there was no significant effect of the purslane genotype on alpha diversity (Shannon index and ASV richness), either for bacteria or fungi, except for fungal richness that was significantly higher in the Spanish (wild) purslane rhizosphere (F = 18.4, p < 0.001).…”
Section: Resultssupporting
confidence: 77%
“…Frontiers in Microbiology frontiersin.org soil microbial diversity and community structure (Huang et al, 2022;Xiao et al, 2022). In this study, it was found that root microorganisms were significantly different among different soybean cultivars.…”
Section: Discussionmentioning
confidence: 69%
“…The different genotypes had significantly different effects on soil microorganisms, and the different genotypes would also affect soil microbial diversity and community structure ( Huang et al, 2022 ; Xiao et al, 2022 ). In this study, it was found that root microorganisms were significantly different among different soybean cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Though many studies have reported the species-specific selection of rhizosphere microbial communities by plants through root traits and exudates ( Costa et al, 2006 ; Sweeney et al, 2021 ; Xiao et al, 2022 ), soil physicochemical properties were considered to be the primary factors affecting rhizosphere fungal community than plant species type (identity) in some studies ( Singh et al, 2007 ; Chen et al, 2019 ). Soil can regulate the rhizosphere microbial community; particularly, soil pH and nutrients are regarded as the key factors influencing the structure of the rhizosphere microbial community ( Philippot et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%